Estimating Shoulder-Complex Mobility - Bertrand Tondu (Applied Bionics and Biomechanics)
Modeling shoulder motions is essential in understanding upper-limb dynamic behavior. However, the mobility of the shoulder complex—in terms of degrees of freedom (DOFs)—is seldom quantified. In this paper we propose applying the theory of mechanisms and, especially, the powerful Grübler–Kutzbach formula to estimate it. This approach requires a rigorous kinematic analysis. So we suggest basing it on a bone schematisation derived from an extension of Dempster’s historical notation associated to mechanical interpretation of the physiological joints involved. In so doing, the proposed shoulder complex mobility leads to justifying a nine-DOF serial-chain upper-limb mode, which extends the classical seven-DOF arm–foream–wrist model and completing it by adding a clavicle-like link with a two-DOF mobility.